Anti-corruption, government subsidies, and investment efficiency - Huili Zhang; Ran An; Qinlin Zhong (China Journal of Accounting Research, 2019)
The problem of corruption in socio-economic development has long been a focus of academics and practitioners. To address this concern in China, the 18th National Congress of the Communist Party of China instituted a new anti-corruption policy. In this paper, we examine the impact of this recently enacted anti-corruption policy on the investment efficiency of subsidized enterprises from the perspective of government subsidies. We conclude that government subsidies have a significant positive impact on the overinvestment behavior of enterprises and that the anti-corruption work done by the government has effectively restrained the excessive investment behavior of government-subsidized enterprises. Further, we find that the anti-corruption policy is more effective in restricting overinvestment in subsidized state-owned enterprises than in non-state-owned enterprises. We examine the impact of the anti-corruption policy on excessive investment caused by government subsidies and enrich the body of research related to investment efficiency. We also provide empirical support for further research on the anti-corruption policy at the macro-market and micro-enterprise levels. The findings highlight the need to establish new cooperation between government and enterprises, to rationalize the distribution of administrative resources, and to promote the sustained and healthy development of the national economy.
Keywords: 650; Anti-corruption; Government subsidies; Investment efficiency; Type of controlling shareholders